Soybean pod shattering resistance allele pdh1 and marker-assisted selection - Shimbwambwa, D.; Nachilima, C.; Hamabwe, S.; Kuwabo, K.; Chigeza, G.; Bilyeu, K.; Kamfwa, K. (2024)
Pod shattering is a major production constraint of soybean [Glycine max (L.)]. The objectives of this study were to (i) estimate heritability for pod shattering resistance, (ii) determine the frequency of the pod shattering resistance allele pdh1 in the International Institute for Tropical Agriculture (IITA) soybean germplasm and Zambian commercial varieties, and (iii) determine the effectiveness of the DNA marker for the pod shattering resistance allele pdh1. A total of 59 genotypes were evaluated for pod shattering in field trials conducted in Malawi and Zambia and genotyped with a marker for pdh1. TGx2002-8FM and TGx2002-9FM were the most resistant among genotypes in early and medium maturity classes and can be used for genetic enhancement of pod shattering resistance in these specific maturity classes. Narrow sense heritability estimates for pod shattering ranged from 0.27 to 0.80. Of the 59 genotypes, 57 (96.6%) carried the resistance allele pdh1 while only two genotypes (3.6%) carried the susceptible allele, suggesting near-fixation of the resistance allele pdh1 in the IITA germplasm. The marker for pdh1 was highly effective in selecting resistant genotypes.